The risk of infections for multiple sclerosis and neuromyelitis optica spectrum disorder disease-modifying treatments: Eighth European Committee for Treatment and Research in Multiple Sclerosis Focused Workshop Review. April 2021. (August 2022) - Tur, Carmen; Dubessy, Anne-Laure; Otero-Romero, Susana; Amato, Maria Pia; Derfuss, Tobias; Di Pauli, Franziska; Iacobaeus, Ellen; Mycko, Marcin; Abboud, Hesham; Achiron, Anat; Bellinvia, Angelo; Boyko, Alexey; et al.
Over the recent years, the treatment of multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) has evolved very rapidly and a large number of disease-modifying treatments (DMTs) are now available. However, most DMTs are associated with adverse events, the most frequent of which being infections. Consideration of all DMT-associated risks facilitates development of risk mitigation strategies. An international focused workshop with expert-led discussions was sponsored by the European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS) and was held in April 2021 to review our current knowledge about the risk of infections associated with the use of DMTs for people with MS and NMOSD and corresponding risk mitigation strategies. The workshop addressed DMT-associated infections in specific populations, such as children and pregnant women with MS, or people with MS who have other comorbidities or live in regions with an exceptionally high infection burden. Finally, we reviewed the topic of DMT-associated infectious risks in the context of the current SARS-CoV-2 pandemic. Herein, we summarize available evidence and identify gaps in knowledge which justify further research.